5-6(a+2)-7+a=

Simple and best practice solution for 5-6(a+2)-7+a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-6(a+2)-7+a= equation:


Simplifying
5 + -6(a + 2) + -7 + a = 0

Reorder the terms:
5 + -6(2 + a) + -7 + a = 0
5 + (2 * -6 + a * -6) + -7 + a = 0
5 + (-12 + -6a) + -7 + a = 0

Reorder the terms:
5 + -12 + -7 + -6a + a = 0

Combine like terms: 5 + -12 = -7
-7 + -7 + -6a + a = 0

Combine like terms: -7 + -7 = -14
-14 + -6a + a = 0

Combine like terms: -6a + a = -5a
-14 + -5a = 0

Solving
-14 + -5a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -5a = 0 + 14

Combine like terms: -14 + 14 = 0
0 + -5a = 0 + 14
-5a = 0 + 14

Combine like terms: 0 + 14 = 14
-5a = 14

Divide each side by '-5'.
a = -2.8

Simplifying
a = -2.8

See similar equations:

| 9x+89=5x-88 | | (3+6i)(3+6i)= | | Z^2-5z+6=0 | | (8+4i)(8-4i)= | | 8x-4x= | | (6-3i)(7-2i)= | | -2.3g=7.13 | | Q=5g+5w | | 40=-1.6m | | 4v^2=36v | | (7-5i)(3-8i)= | | 1*x= | | 5i(6-2i)= | | 11x-13=97 | | 5x+2=25 | | 4i(4-2i)= | | 4(x-2)-6=-2(x+3) | | (3+8i)-(8-3i)= | | -2+7=21 | | 6(y-3)=2y-42 | | 8x^2+61x-24=0 | | (7-8i)+(1+7i)= | | x^3+4x^2+8x+8=0 | | 2y=3.5+y | | 2y=-7+y | | 5x=2(x+5) | | 8x^2-35x+12=0 | | x-43=3,70 | | 16=-3v+34 | | 9=2z-4 | | 6(5k-8)-20=(2k-3)+3k | | 1.6m=40 |

Equations solver categories